Table of Contents - Board, Editorial (Law, State and Telecommunications Review, 2018)
Dear Reader, We are pleased to introduce the tenth volume of the Law, State and Telecommunications Review (LSTR). In this issue, the journal published a number of original articles on topics relevant to telecommunications from a myriad of interdisciplinary perspectives, gathering scholars from Algeria, Brazil, Spain, France, India, Iran and Mexico. In this issue, we are delighted to include articles on regulatory state and judicial decisions in telecommunications in Mexico, consumer protection from abuses in commercial communications, legal assessment on personal data in the European Union, the right of concerned persons in the personal data process in France and Europe, OTTs unfair tax practices, Internet regulation, secure channel for data exchanging, suppression of mutual coupling in high frequency wave applications, use of SEECH algorithm in wireless sensor networks, and Brazil’s statutes, regulations and judicial decisions on telecommunications. For future issues, we will continue to publish articles on all relevant areas of telecommunications. We hope you have enjoyed reading the first decade of this journal, and we look forward to an eleventh volume to be released on May 2019. Sincerely, Prof. Marcio Iorio Aranha Editor-in-Chief, The Law, State and Telecommunications Review On behalf of the Editorial Board